2010
DOI: 10.1061/(asce)te.1943-5436.0000143
|View full text |Cite
|
Sign up to set email alerts
|

Road Roughness and Whole Body Vibration: Evaluation Tools and Comfort Limits

Abstract: An important element of achieving quality in a road network is the control of vehicle vibration due to pavement roughness and road irregularities. Scientific literature and international standards suggest that we evaluate these phenomena by measuring the whole body vibration (WBV) on the road user, but, for the practical aims of road engineering, this expression has to be related to road unevenness indexes, especially the most common one (the international roughness index, IRI). This index, in turn, is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 2 publications
8
93
1
8
Order By: Relevance
“…DLI, instead, is based on the assessment of the loads induced by trucks on road pavement due to the presence of irregularities. In addition, the ride quality assessment, that is, the main topic of the ISO 2631 standard, was evaluated by simulations, calculating the whole-body vibration perceived by road users inside a vehicle riding on a roughness pavement, as described by Cantisani and Loprencipe [10].…”
Section: Introductionmentioning
confidence: 99%
“…DLI, instead, is based on the assessment of the loads induced by trucks on road pavement due to the presence of irregularities. In addition, the ride quality assessment, that is, the main topic of the ISO 2631 standard, was evaluated by simulations, calculating the whole-body vibration perceived by road users inside a vehicle riding on a roughness pavement, as described by Cantisani and Loprencipe [10].…”
Section: Introductionmentioning
confidence: 99%
“…ISO 2631 (1997) was applied to calculate the vertical acceleration (a wz ). The speed-related a wz thresholds proposed by Cantisani and Loprencipe (2010) were adopted for the analysis of the data (Table 4). The road roughness versus speed versus vertical acceleration was plotted on three-dimensional graphs to indicate the impact of speed on the vertical acceleration data.…”
Section: Resultsmentioning
confidence: 99%
“…The vertical accelerations were influenced by the road roughness, as well as by the speed of the vehicle. Cantisani and Loprencipe (2010) indicated that a section of surface failure will register a high road roughness, but depending on the speed the vehicle travels over that surface failure, the accelerations could be high and low. Therefore, Cantisani and Loprencipe (2010) indicated that if the vehicle speed was reduced, a higher level of roughness could be tolerated.…”
Section: National Road Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile analysis allows evaluating general ride characteristics referring to standards, comfort and safety [25] and choosing pavement sections where the warning values of the previous evaluation are reached and maintenance works needed [26][27][28][29].…”
Section: Methodology and Case Of Studymentioning
confidence: 99%